2018
DOI: 10.1007/s12046-018-0849-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scale size, orientation type and dispensing method on void formation in the CUF encapsulation of BGA

Abstract: Prediction of void occurrence during capillary underfill encapsulation process is vital to avoid package failure due to incomplete filling during the encapsulation process. Two design variables, namely the gap height and package orientations, together with different types of industrial standard design of dispensing methods were identified as possible influences to the void formation in encapsulated package. In this paper, all these factors have been closely related to the void formation and subsequently the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
(39 reference statements)
0
17
0
1
Order By: Relevance
“…Ho et al (2007) reported that the reduction of void occurred can be achieved by increasing the plasma time and underfill dispense temperature, as well as selecting a smoother substrate surface. The more recent studies attempted to understand the void formations at various operating conditions, for instance bump arrangement (Abas et al , 2016) and dispensing type (Abas et al , 2018; Ng et al , 2017a, 2017b). Nonetheless, there is no detailed discussion on the mechanism of void formation during underfill process particularly from the microscopic aspect being proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Ho et al (2007) reported that the reduction of void occurred can be achieved by increasing the plasma time and underfill dispense temperature, as well as selecting a smoother substrate surface. The more recent studies attempted to understand the void formations at various operating conditions, for instance bump arrangement (Abas et al , 2016) and dispensing type (Abas et al , 2018; Ng et al , 2017a, 2017b). Nonetheless, there is no detailed discussion on the mechanism of void formation during underfill process particularly from the microscopic aspect being proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The functions of underfill encapsulation include to relief the residual stress due to thermal mismatch, to serve as a protective layer and to promote the package's reliability [2][3]. There are various researches conducted to optimize the underfill process through package design [4][5][6][7] as well as to resolve the issues of incomplete filling [8] and void defect [7,9]. The most common and straightforward approach in underfill research is through experiment [2][3][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the concerns of cost and limited versatility that arise from the underfill experiment prompt to the implementation of numerical simulation. There are variety of numerical schemes adopted in the underfill simulation, for instance, finite volume method (FVM) [6,[12][13], finite element method (FEM) [14], fluid/structure interaction (FSI) [8], discrete phase model (DPM) [10], lattice Boltzmann method (LBM) [7] and Petrov-Galerkin (PG) method [15]. As the underfill flow simulation usually based on the full flip-chip, therefore the numerical simulation took substantial long time to complete.…”
Section: Introductionmentioning
confidence: 99%
“…As the underfill fluid is driven into the gap via capillary action, the underfill process usually takes a substantial amount of time to complete (Zhang and Wong, 2004). Technically, a slow underfill process is unfavorable, as it would incur additional manufacturing costs, while the package is also prone to void defects (Abas et al, 2018). It can be seen that the productivity and performance of the underfill process are strongly dependent on the filling time.…”
Section: Introductionmentioning
confidence: 99%
“…Such adoption of imitation chips was largely attributed to cost concerns, versatility in parameter variation and flow visualization. Moreover, Khor et al (2012c) pioneered the usage of a proportionally scaled-up imitation chip to experimentally visualize the underfill flow, which was also successfully being used in other subsequent underfill experiments (Khor et al, 2012b;Ng et al, 2017a;Abas et al, 2018;Ng et al, 2018). Among various scaled-up imitation underfill experiments, the scaling validity of the scaled-up imitation system was only being analyzed by Ng et al (2018) through the dimensionless number similarity.…”
Section: Introductionmentioning
confidence: 99%